Next generation genetic testing in the diagnostics of neurological disease in Southwest Finland in 2010–2021 : a register-based study - Loukiainen, Saga (My University, 2024)
Neurological disorders are heterogeneous and sometimes challenging to diagnose. Next generation sequencing (NGS) panels and exome sequencing methods are increasingly advocated as first-tier genetic investigations. In this retrospective, single-centre, register-based study we investigated the use of NGS based investigations in the diagnostics of adult neurological disease at Turku University Hospital (TUH, Turku, Finland) during 2010–2021. We identified patients who had undergone any genetic testing to investigate a neurologic disease in 2010–2021. NGS gene panel studies and clinical or whole exome investigations were scrutinised further. Data were collected from the TUH electronic medical records. We identified N=844 patients (347 men and 497 women) who fulfilled the initial inclusion criteria. In this group, 331 NGS panels, 77 clinical exome studies, and 22 whole exome analyses were performed. The median age at the time of first included genetic test was 45 years (range: 16–96 years). The diagnostic rate was 18% for all NGS techniques; 23 % for whole exome studies, 21 % in NGS panels, and 10 % in clinical exome sequencing. Among different patient groups, the diagnostic yield was highest in developmental and intellectual disorders (39 %), second highest in neuromuscular disorders (38 %), and lower in epilepsy and ataxia (13 % and 10 %). Among neurological disorders, the diagnostic yield of genetic testing differs between different patient phenotypes and on the genetic testing selection. Further studies are needed to determine optimal strategies, with highest yield and lowest cost, for genetic investigations in neurological disorders.
Keywords: diagnostics, exome sequencing, neurological disease, next generation sequencing